The right to a healthy environment through collective action in Mexico: Retos y perspectivas - Bautista Arciniega, Luis Alberto; García González, Conrado; García Espinoza, Elizabeth (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The human right to a healthy environment is part of the so-called rights of solidarity, so the scope of the sphere of ownership and enforcement is collective. The innovation of access to justice of the right to a healthy environment through collective means, brought important reforms in the Political Constitution of the United Mexican States and to the secondary legal systems, by introducing new figures and legal concepts, which redesigned the acculturation of the legal practice in the country and the action to make effective the access to justice of this right.